Thermal Hysteresis in Melting–Solidification of Nanoparticles - Victor M. Burlakov (Applied Sciences, 2023)
The aim of this paper is the development of a qualitative understanding of thermal hysteresis, namely the difference between the melting <semantics>Tm</semantics> and solidification <semantics>Ts</semantics> temperatures of nanoparticles as a function of the particle size. In contrast to the melting temperature, the determination of the absolute value of the solidification temperature for nanoparticles is generally more difficult and subjected to significant uncertainties. In this study, we implemented a very generic approach based on classical nucleation theory and define the thermal hysteresis for a nanoparticle relative to its value for a much larger ‘reference’ particle made of the same material. The obtained thermal hysteresis is found to vanish when decreasing the nanoparticle size. The approach is illustrated using the examples of gold, bismuth, and platinum nanoparticles.